THEORETICAL RESEARCH OF THE RECIPE OF SUPPLEMENTARY MATERIAL OF TECHNOLOGICAL PURPOSE FOR ENSURING ECOLOGICAL BEZ-PEPYKHYRA VYROPYRA: Array - Varlamov, Y.; Kotukh, V.; Palyeyeva, K. (Municipal economy of cities. Series: «Economy science», 2020)
In the manufacture (repair) of products of transport pipeline systems, auxiliary materials are widely used, which play the role of lubricants, cooling, cleaning and other substances. Special requirements are imposed on the composition of such substances, which are developed in accordance with the technological instructions, since they are, as a rule, chemically active, surfactants of organic and inorganic origin. Therefore, not only the quality of processing of structural elements of transport pipeline systems, but also the environmental safety of the technological process of their manufacture (repair) depends on the composition and mass fraction of ingredients in these substances. Of particular importance in solving problems on this problem belongs to the theory of predicting the formation of the composition of effective auxiliary materials, assessed by technological, economic, sanitary and hygienic and other indicators that are directly related to the formulation of these materials. The theoretical foundations and methods for creating auxiliary materials for technological purposes in the practice of specialized enterprises are implemented using the example of a simplified technological scheme. According to this scheme, the action of each source of deviations (errors in the composition of the auxiliary material) is evaluated separately, and the other sources are “off,” that is, the principle of superposition is implemented. For a qualitative reflection of the technological uniformity of any two constituent ingredients in terms of their influence coefficients, the concept of "intersection" is used, and all possible intersections between pairs of constituents form a square matrix of intersections of dimensions. The level of effective homogeneity, which predetermines the quality of the auxiliary material for technological purposes, depends on two groups of indicators that equally affect this effective homogeneity. Thus, any variant of the formulation of an auxiliary material consisting of groups of constituents with the maximum level of objective closure always corresponds to a certain variant of an ordered series of ingredients.